Rivalitas Semu Elite Politik pada Pemilukada Gubernur Provinsi Jawa Timur 2018 - Muhammad Aditya Pradana (Neolectura, 2021)
Rivalry and elite cooperation in Indonesia exist due to the existence of interests between groups of actors that intersect with each other in various aspects. That the elite always tries to create consensus through cooperation on the calculation of profits even though there is rivalry between the elites who intersect. This can be seen from the post-conflict local elections in East Java in 2008, 2013, and 2018. In the 2008 and 2013 East Java regional elections, Soekarwo became Khofifah's rival. However, in the 2018 East Java election, Soekarwo turned to support Khofifah and decided not to support his deputy for two periods, namely Saifullah Yusuf. This study wants to see the factors behind elite rivalry and cooperation, especially in the context of the 2018 East Java Regional Election. This research uses qualitative methods. In addition, this research also uses the theory of antagonistic cooperation, boundary control theory, party-led transition, and integration theory and elite circles. The results of this study show that there is a role for the national elite, in this context the DPP of the Democratic Party and the influence of President Joko Widodo in the transition of Soekarwo's support to Khofifah. In addition, this study also found that there was a relationship of interdependence between Seokarwo and Khofifah. Soekarwo hopes that what he is doing can be continued by Khofifah, while Khofifah depends on the full support of Soekarwo so that he can win in an area that he has never won before.